Peran Lingkungan Keluarga melalui Pola Asuh Orang Tua dalam Meningkatkan Children Wellbeing Anak Usia Dini - Risti Apriani; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to examine the role of the family environment, specifically through parenting styles, in enhancing children’s well-being during early childhood. Children’s well-being refers to a state of well-being that encompasses physical, psychological, and social aspects, which is significantly influenced by the child’s immediate environment, particularly the family. This study employs a qualitative approach using a literature review method, drawing from various scientific journals, books, and previous research findings. The findings indicate that the family, as the first and primary environment, plays a dominant role in shaping children’s well-being. Parental parenting styles are a key factor, with the authoritative (democratic) style proven to be the most effective in supporting children’s emotional, social, and psychological development. Conversely, authoritarian and permissive parenting styles tend to have negative impacts on children’s development. A warm, loving family environment, coupled with good communication, can enhance children’s sense of security, self-confidence, and emotional regulation skills. Thus, the application of appropriate parenting styles within the family environment is crucial for supporting the optimal achievement of children’s well-being in early childhood